Application of Response Surface Methods for Evaluating the Interactions of Soman, Atropine, and Pralidioxime Chloride - CARTER, W. H.; JONES, D. E.; CARCHMAN, R. A. (Toxicological sciences, 1985)
Application of Response Surface Methods for Evaluating the Interactions of Soman, Atropine, and Pralidioxime Chloride. CARTER, W. H., JR., JONES, D. E., AND CARCHMAN, R. A. (1985). Fundam. Appl. Toxicol. 5, S232–S241. Response surface methods were employed to model survival data obtained in guinea pigs following subcutaneous exposure to soman (GD; 30–84.6 Mg/kg) with various treatment regimens (i.e., atropine/pralidioxime chloride [ATR/2-PAM] combinations, given im, 1 min post-GD). The analysis of the proportions of surviving animals in the various groups revealed that the use of individual treatment agents (i.e., ATR or 2-PAM) was effective in increasing survival. The level of GD exposure altered the nature of the ATR/2-PAM interaction. Exploration of the response surface indicates that the optimal treatment combinations (>94% survival) of ATR/2-PAM change as a function of GD exposure in the following manner GD 30 μg/kg-ATR/2-PAM, 217 mg/kg/0 mg/kg; GD 42.4 μg/kg-179/29 mg/kg; GD 60 μg/kg-148/83 mg/kg; GD 84.6 μg/kg-168/150 mg/kg. At higher exposures of GD (>42.4 μg/kg), therapeutic synergy was observed with the use of the treatment combinations, as compared to optimal single agent treatments. Evaluation of the apparent toxicities of treatment combinations can also be determined in this procedure. RSM is not geometrically restricted by the number of variables under consideration. A variety of experimental designs, when used in conjunction with RSM, permit the modeling of multiple responses and provide estimates of optimal therapeutic modalities subject to constraints (e.g., behavioral toxicity).